Alignment of palatally impacted canine with open window technique and modified K-9 spring - Dipti Shastri; Amit Nagar; Pradeep Tandon (Wolters Kluwer Medknow Publications, 2014)
The patient was an 18-year-old female who had an Angle Class I malocclusion with a left palatally impacted maxillary canine. The orthodontic treatment of a palatally impacted canine is aimed at bringing the tooth into its correct position in the dental arch without causing any periodontal damage. To achieve this goal, a variety of surgical and orthodontic techniques have been proposed in relation to the position of the impacted tooth and there are various treatment methods used for traction. The duration of the traction was 3 months and alignment duration was 12 months the total treatment time was 15 months. In the following case, we presented that maxillary palatally impacted canine was brought into the arch with open window method for canine exposure and modified K-9 spring for traction, that is simple spring for orthodontic traction of the palatally impacted canines.